Implementasi SPMI dalam Meningkatkan Mutu Sekolah di MAN 2 Rembang - Irnawati, Diyah; Haryati, Titik; Wuryandini, Endang (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study aims to analyze the implementation of the Internal Quality Assurance System (SPMI) in improving school quality at MAN 2 Rembang. A descriptive qualitative approach was used to describe the roles of the principal, vice principal, teachers, students, madrasah committee, and parents in the SPMI implementation cycle, which includes self-evaluation, planning, implementation, monitoring, and follow-up. The results show that the implementation of SPMI at MAN 2 Rembang has had a positive impact on the quality of learning, madrasah management, and student character development. However, there are obstacles in the form of limited facilities and not optimal involvement of all elements of education. Collaboration and communication among stakeholders are the keys to successful SPMI implementation. This research provides a practical contribution for other madrasahs in integrating SPMI to realize a better quality of education.